Autogeneic RNA-electroporated CD40-ligand activated B-cells from hepatocellular carcinoma patients induce CD8+ T-cell responses ex vivo - Shen, S.; Xu, Z.; Qian, X.; Ding, Y.; Yu, L.; Liu, B. (Experimental Oncology, 2007)
Since dendritic cells (DCs) constitute only 0.1–0.5% of human peripheral blood mononuclear cells (PBMCs), and generation of DCs from monocytes or stem cells is difficult and expensive, we choose B-lymphocytes as an alternative, cost-effective source of antigen presenting cells (APC). Aim: To induce specific CTLs response ex vivo by CD40L activated B-cells (CD40-B) transfected with hepatocellular carcinoma (HCC) total RNA. Methods: To induce CD40-B PBMCs of patients with HCC were isolated by Ficoll technique and cultured in RMPI 1640 supplemented with 10% fetal calf serum (FCS), sCD40L (2 µg/ml), recombinant human interleukin-4 (IL-4) (4 ng/ml). The expression of CD80 and CD86 was evaluated by flow cytometry. The level of interleukin-12 (IL-12) produced by cultured B-lymphocytes was measured using enzyme-linked immunosorbent assay (ELISA). HCC patient’s T-lymphocytes were obtained from PBMCs cultured in RMPI 1640 supplemented with 10% FCS, 2 ng/mL IL-4 and 10 ng/ml IL-7. CD40-B transfected with tumor total RNA isolated from HCC cells were used to induce specific CTL proliferation. The level of IFN-g was measured using ELISA and the expression of CD8 was determined by FCAS. Specific cytotoxicity was measured using MTT method. Results: The results show that the activated B-lymphocytes were easily expandable and formed large clones, and a high expression of CD80/CD86 and a high IL-12 secretion by CD40-B was registered. CD40-B transfected with tumor total RNA can induce CTLs to express CD8 and generate IFN-g at high levels. Compared to the control group, the specific cytotoxicity of CTLs was up-regulated. Conclusion: These findings demonstrate that CD40-B-cells electroporated with total RNA derived from carcinoma cells can be used as alternative APC for the induction of antigen-specific CD8+ T-cell responses, which might be used in HCC immunotherapy.